2015
DOI: 10.1128/jcm.03507-14
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Infections and Rifampin Heteroresistance among Mycobacterium tuberculosis Clinical Isolates

Abstract: Mixed infections and heteroresistance of Mycobacterium tuberculosis contribute to the difficulty of diagnosis, treatment, and control of tuberculosis. However, there is still no proper solution for these issues. This study aimed to investigate the potential relationship between mixed infections and heteroresistance and to determine the high-risk groups related to these factors. A total of 499 resistant and susceptible isolates were subjected to spoligotyping and 24-locus variable-number tandem repeat methods t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
1
29
0
2
Order By: Relevance
“…Polyclonal M. tuberculosis infections may have a negative impact on drug resistance testing performed by both phenotypic ( e.g., proportional test) and genotypic methods ( e.g., GeneXpert MTB/RIF)1112. Another problem for diagnosis and treatment of TB patients, which is more difficult to detect by the usual phenotypic DST is hetero-resistance13.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal M. tuberculosis infections may have a negative impact on drug resistance testing performed by both phenotypic ( e.g., proportional test) and genotypic methods ( e.g., GeneXpert MTB/RIF)1112. Another problem for diagnosis and treatment of TB patients, which is more difficult to detect by the usual phenotypic DST is hetero-resistance13.…”
Section: Discussionmentioning
confidence: 99%
“…Manu2, one of the genotypes sorted by spoligotype number, was found to be significantly associated with mixed infections among the 499 tested clinical isolates (odds ratio 47.72; confidence interval 9.68–235.23; p < 0.01). Four isolates (1.37%) were confirmed to be hetero-resistant, out of which three (75%) were caused by mixed infections and belonged to Manu2 [ 64 ]. That study first revealed that Manu2 was the most predominant genotype in cases of mixed infections and potentially the main reason behind development of hetero-resistance.…”
Section: Bacterial Changesmentioning
confidence: 99%
“…[3,4] Polyclonal infections may be associated with Hetero-resistance. [5][6][7][8]. , showed that false-negative results using Gene-Xpert MTB/RIF were significantly associated with mixed infections and that it fails to detect rifampicin (RIF)resistance in vitro when resistant sub-populations accounted for <90%.…”
Section: Introductionmentioning
confidence: 99%